Decision Support System for Selection of Outstanding Students at Angkasa Maros High School Using the TOPSIS Method - Vivek Sharma; Bangri, Nardo Azalio; Iskandar, Akbar (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
This study aims to develop a Decision Support System (DSS) to aid in the selection of outstanding students at Angkasa Maros High School. The TOPSIS method was selected for its capability to handle diverse criteria, enabling assessments based on academic and non-academic achievements, leadership qualities, and positive attitudes. Data were collected through observational and documentary methods, gathering student achievement data and other relevant factors, which were then inputted into the system to compute relative scores for each student based on predetermined criteria weights. This process resulted in a ranking of students according to their performance against these criteria. The research findings indicated that the DSS achieved an overall percentage score of 90.3% in selecting outstanding students using the TOPSIS method, demonstrating effective system implementation and significant benefits in the student selection process. The study's outcomes are expected to provide objective and accurate recommendations for selecting outstanding students at Angkasa Maros High School, serving as a guide for the school in identifying students with high potential and facilitating more effective and efficient decision-making. Additionally, the research offers valuable insights for Angkasa Maros High School to enhance educational quality, maximize student potential development, and produce graduates capable of competing at national and international levels.